Studies on the Contribution of Weeds and their Management to the Prevalence of Pineapple Mealybugs - Tachie – Menson, Josiah Wilson (2012)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science, 2012